The Effect Of Profitability, Leverage, And Company Size Financial Distress In Healthcare Service Companies Listed On IDX - Azhar, Iqlima; Lubis, Nurliza; Nurjanah, Siti (Management Department Universitas Islam Negeri Sumatera Utara, 2024)
This research examines the influence of profitability, leverage, and company size on financial distress among healthcare service companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Using a quantitative approach, the study utilizes secondary data from the IDX and official company websites. The sample includes 14 healthcare service companies selected through purposive sampling. Employing multiple regression analysis with the Ordinary Least Square (OLS) method, the findings reveal that profitability positively and significantly impacts financial distress (0,034 < 0,05), leverage negatively and significantly impacts financial distress (0,008 < 0,05), while company size shows a positive but insignificant impact (0,610 > 0,05). The regression model explains 62% of the variance in financial distress.These results suggest that enhancing profitability can reduce the risk of financial distress, while managing leverage levels is critical for maintaining financial stability. The findings offer practical insights for financial managers and stakeholders in the healthcare sector to adopt robust financial planning and monitoring strategies to mitigate distress risks, thereby ensuring operational sustainability. For policymakers, the study underscores the importance of creating supportive financial frameworks for healthcare companies, particularly in volatile economic conditions.Keywords: Company Size, Financial Distress, Leverage, Profitability